Effect of Magnolol on the Function of Osteoblastic MC3T3-E1 Cells - Eun Jung Kwak; Young Soon Lee; Eun Mi Choi (Mediators of Inflammation)
Objectives. In the present study, the ability of magnolol, a hydroxylated biphenyl compound isolated from Magnolia officinalis, to stimulate osteoblast function and inhibit the release of bone-resorbing mediators was investigated in osteoblastic MC3T3-E1 cells. Methods. Osteoblast function was measured by cell growth, alkaline phosphatase activity, collagen synthesis, and mineralization. Glutathione content was also measured in the cells. Bone-resorbing cytokines, receptor activator of nuclear factor-κB ligand (RANKL), TNF-α, and IL-6 were measured with an enzyme immunoassay system. Results. Magnolol caused a significant elevation of cell growth, alkaline phosphatase activity, collagen synthesis, mineralization, and glutathione content in the cells (P<0.05). Skeletal turnover is orchestrated by a complex network of regulatory factors. Among cytokines, RANKL, TNF-α, and IL-6 were found to be key osteoclastogenetic molecules produced by osteoblasts. Magnolol significantly (P<0.05) decreased the production of osteoclast differentiation inducing factors such as RANKL, TNF-α, and IL-6 in the presence of antimycin A, which inhibits mitochondrial electron transport and has been used as an ROS generator. Conclusion. Magnolol might be a candidate as an agent for the prevention of bone disorders such as osteoporosis.